2016
DOI: 10.5536/kjps.2016.43.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Growth Patterns of 25 Commercial Strains of Korean Native Chicken

Abstract: Prediction of growth patterns of commercial chicken strains is important. It can provide visual assessment of growth as function of time and prediction body weight (BW) at a specific age. The aim of current study is to compare the three nonlinear functions (i.e., Logistic, Gompertz, and von Betalanffy) for modeling the growth of twenty five commercial Korean native chicken (KNC) strains reared under a battery cage system until 32 weeks of age and to evaluate the three models with regard to their ability to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In growth curve studies in native chickens, various models were introduced as the best model to describe the growth curve. The Gompertz model for Nigerian native chickens (Adenaike et al, 2017), slow-growing chickens in China (Zhao et al, 2015), Poland medium-growing chickens (Michalczuk et al, 2016), Logistic model for slow-growing chickens in the organic system (Eleroglu et al, 2014), Von Bertalanffy for Korean native chickens (Manjula et al, 2016), and Lopez for Khazak chickens (Faraji-Arough et al, 2019) was reported. Although, Faraji-Arough et al ( 2019) introduced the Lopez model for Khazak chickens that in contrast with present results.…”
Section: Discussionmentioning
confidence: 99%
“…In growth curve studies in native chickens, various models were introduced as the best model to describe the growth curve. The Gompertz model for Nigerian native chickens (Adenaike et al, 2017), slow-growing chickens in China (Zhao et al, 2015), Poland medium-growing chickens (Michalczuk et al, 2016), Logistic model for slow-growing chickens in the organic system (Eleroglu et al, 2014), Von Bertalanffy for Korean native chickens (Manjula et al, 2016), and Lopez for Khazak chickens (Faraji-Arough et al, 2019) was reported. Although, Faraji-Arough et al ( 2019) introduced the Lopez model for Khazak chickens that in contrast with present results.…”
Section: Discussionmentioning
confidence: 99%